THE ACCEPTANCE OF INTERNATIONAL AID IN MANAGEMENT OF NATURAL DISASTERS IN INDONESIA - Rudiyanto, Teguh (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2023)
The absence of clear budgeting regarding disaster management in the State Revenue and Expenditure Budget (APBN) is a condition that must be studied using the perspective of the government's fulfillment of human rights. Meanwhile, the involvement of charitable institutions, social communities and even other countries in the context of handling national disasters is a specific issue that will be discussed. The formulation of the problem raised in this research is (1) the obstacles faced in implementing the receipt of international aid in the process of handling natural disasters in Indonesia and (2) the regulation of international law on the receipt of international aid in managing natural disasters in Indonesia. This research resulted in the conclusion that there are still various countries which, although unable to provide humanitarian assistance to victims of natural disasters in their own countries, still have doubts about granting permits to enter humanitarian aid from abroad. The declining quality of the environment